Treatment of highly fatal extensive childhood mucormycosis with complications: A success story - Aakash Chandran Chidambaram; Jaikumar Govindaswamy Ramamoorthy; Reena Gulati; Bhawana A Badhe (Wolters Kluwer Medknow Publications, 2021)
Background: Mucormycosis is a highly fatal infection that affects immunocompromised individuals. Treatment is difficult and mortality is high when associated with complications. It is rare as a presenting feature of diabetes mellitus (DM) in children. Clinical Description: We describe a child who presented with extensive rhino-orbital invasive mucormycosis and subsequently diagnosed as Type 1 DM. She further developed cavernous sinus thrombosis and internal carotid artery thrombosis known to be associated with very high risk of mortality. Management: Aggressive medical management with posaconazole and liposomal amphotericin B for 12 weeks and early debridement of orbito-cerebral lesions led to complete resolution. Conclusion: Saving children with complicated extensive invasive mucormycosis is possible with aggressive prolonged antifungal therapy and early debridement of lesions.